Membangun Reputasi Islami yang Otentik: Branding SD IT Madani Islamic School Payakumbuh sebagai Sekolah Berbasis Fitrah Genetik - Novita, Oten; Karim, Hamdi Abdul (YASIN, 2025)
Although Islamic school branding has been the focus of several studies, research that specifically integrates value-based Islamic branding with a genetic fitrah-based educational approach at the elementary school level remains very limited. This study aims to analyze the process of constructing an authentic Islamic reputation at SD IT Madani Islamic School Payakumbuh through value habituation, teacher role modeling, personalized learning, humanistic public communication, and a child-friendly religious school culture. A qualitative approach with a descriptive case study design was employed. Participants consisted of the principal, six teachers, twelve students, and eight parents selected using purposive sampling. Data were collected through participatory observation, in-depth interviews, and documentation, and were analyzed using the Miles, Huberman, and Saldana model. The findings show that the school’s Islamic reputation is built through consistent habituation of ibadah, reinforcement of adab, the development of fitrah portfolios as the basis for mapping students’ potentials, and transparent, empathetic public communication; a safe, child-friendly school culture further strengthens the institution’s image. These results contribute to the expansion of the concept of practice-embedded Islamic branding and underscore the importance of value consistency in fitrah-based educational practice. The study recommends strengthening teachers’ capacities and implementing long-term evaluation of fitrah-based education to ensure the sustainability of an authentic Islamic reputation.